Diagnostic efficacy of dual-energy CT virtual non-calcium technique in the diagnosis of bone marrow edema of sacroiliac joints in ankylosing spondylitis - Hongyue Lu; Zhi Li; Ziheng Liang; Yuqi Liu (Journal of Orthopaedic Surgery and Research)
Abstract Objective In-depth investigation of the diagnostic performance of dual-energy CT (DECT) virtual non-calcium (VNCa) technique for sacroiliac joint bone marrow edema (BME) in patients with ankylosing spondylitis(AS). Methods A total of 42 patients with AS)who underwent sacroiliac joint MRI and DECT scans on the same day at our Rheumatology and Immunology Department between August 2022 and June 2023 were selected. Using MRI as the reference standard, the presence of BME on the iliac and sacral surfaces was evaluated, resulting in the categorization of patients into BME-positive and BME-negative groups. Subsequently, the DECT scan data was processed using the “Bone Marrow” algorithm to generate VNCa color-coded images of the bone marrow. The diagnostic performance of DECT in detecting BME was assessed through visual qualitative evaluation and objective quantitative analysis. Results Visual qualitative assessment analysis showed good agreement between the results of BME analysis on virtual non-calcium images and MRI images by both physicians (Kappa > 0.61). The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of visual qualitative assessment for BME by Physicians A and B were as follows: iliac facet [(92.5%, 88.6%, 88.1%, 92.9%, 90.5%), (90.0%, 90.9%, 90.0%, 90.9%, 90.5%)], sacral facet [(88.4%, 87.8%, 88.4%, 87.8%, 88.1%), (90.7%, 85.3%, 86.7%, 89.7%, 88.1%)].In terms of objective quantitative analysis, the CT values of the edematous areas on the iliac and sacral surfaces were (-41.4 ± 15.9) Hu and (-38.8 ± 19.7) Hu, respectively, while the CT values of normal bone marrow areas were (-79.6 ± 18.2) Hu and (-72.8 ± 14.8) Hu, respectively. The CT values of the edematous areas were higher than those of the non-edematous areas. Based on the receiver operating characteristic curve analysis, the area under the curve for the iliac and sacral surfaces were 0.90 and 0.89, respectively. The optimal CT cutoff values were − 57.4 Hu and − 56.8 Hu, with corresponding sensitivities of 92.5% and 86.4% and specificities of 90.7% and 87.8%. Conclusion The DECT VNCa technique has a high diagnostic efficacy in the diagnosis of BME in the sacroiliac joints in ankylosing spondylitis in terms of visual qualitative assessment and objective quantitative analysis.